PENGARUH BENTUK KANOPI POHON TERHADAP KUALITAS ESTETIKA LANSKAP JALAN - Garsinia Lestari; Andi Gunawan (http://arl.faperta.ipb.ac.id/, 2010)
Trees in streetscape functionally and aestheticallyhave significant role. Trees can create aesthetical value as well as increase environmental quality by their character. Canopy shape and color of flower are visually the most prominent character of trees The objective of this study are to observe and evaluate on visual aesthetical quality of trees in streetscape, and on visual perception of tree canopy shape and its flower. The methods to collect data were conducted by survey, reference study, and simulation on streetscape. The estimation of aesthetical qualitywas done by applying Scenic Beauty Estimation and Semantic Differential. The study has shown result that tree canopy shape becomes the most influence element of respondent’s assessment on landscape design. The use of trees with different canopy shapes and color change of tree parts during flowering have given diverse space impression and psychological effect of the same site.